The Effects of Using Speaky Android Application on EFL Students’ Autonomous Learning - MOSTEFA DAOUADJI, MOUNA (My University, 2018)
21st century learners are willing to be autonomous and are seeking more responsibility for their own learning. Since they are technologically friendly, they rely mostly on technology for communicating and interacting via watching movies, listening to music, using applications and social networking sites. As for modern EFL learners, they are comfortable when using their laptops , phones, or I-pads, to practice their English. To investigate the use of mobile phones applications, this study is intended to find out the effect of using one interesting android application, “Speaky”, on first year master students of language and communication. The sample for the study comprised 24 EFL students of Abd El Ibn Badis University, Mostaghanem . As an experiment, the learners were asked to use Speaky application for 4 weeks, and then a questionnaire was delivered to the students to collect the data. The results of the study revealed that the learners did become autonomous and in charge of their learning process . Another significant result revealed in this study showed that the majority of the participants agreed on the fact that “Speaky” would significantly help them in learning English.
The Case of First Year Students Master of Language and Communication Students
Keywords: Autonomous learners; Speaky; EFL modern learning